Sustainable E-Government as an Effort to Improve Indonesia's Global Competitiveness - Renti R. Budiman; Teguh Kurniawan (Budapest International Research and Critics University, 2022)
The Worldwide Governance Indicators (WGI) The World Bank has stated that one of the supporting factors for governance to increase the competitiveness of a country is quality public services that can provide multidimensional benefits to stakeholders. Sustainable e-Government is the innovation and use of ICT by the government to promote and provide better-integrated services, not limited to short service life, and flexible to changes and needs. This article aims to explain how efforts are made to achieve sustainable e-Government. The research method used is a qualitative method through literature study. The results of the study explain that achieving sustainable e-Government includes at least five critical dimensions which consist of legal support, simplification of bureaucracy or institutions; institutional and regulatory framework, organizational set-up and culture, a comprehensive technology infrastructure through e-government architecture Enterprise Architecture (EA), literacy skills of ICT of human resources, and cross-organizational collaboration.